ESG Impact on Firm Performance and Investment Efficiency Moderated by Board Cultural Diversity in Asean's Emerging Markets - Ayu Nindita, Safira; Hanggraeni, Dewi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The study examines whether ESG performance improves Firm performance and Investment Efficiency (IE). The study also explores if Board Cultural Diversity (BCD) moderates ESG-Firm Performance and ESG-IE. A panel data collection of 129 nonfinancial Asean-5 enterprises from 2018 to 2022 was used. GLS regression is used to empirically test hypotheses and analyse data. ESG affected ROA and IE but not Tobin’s Q. Additionally, board cultural diversity moderated ESG-ROA interaction. In contrast, BCD cannot moderate ESG-IE relationships. The findings have implications for investors analysing corporate investment management and for stakeholders aware of ESG policies and BCD's impact on firm performance